Speech intelligibility in 4-5 year old children - Leila Ghasisin; Azade Ghasemi; Farnoosh Moobed; Akbar Hassanzade (Vesnu Publications, 2010)
Introduction: Speech intelligibility is the measure of the effectiveness of speech. The Speech intelligibility has important clinical implication including the following: Determining if intervention is needed, setting intervention goals and evaluating effectiveness of intervention. The goal of this study was to measure Speech intelligibility in 4-5 year old children. Materials and Methods: It was a descriptive analytic -cross sectional study .The research group consistent of 70 children (35 girls, 35boys(, that were selected by simple random method among five districts of Isfahan. Two kindergartens from each district were selected accidentally and speech samples of seven children from each kindergarten were analyzed to determine Speech intelligibility. Results: Mean of Speech intelligibility percentage was 97.53 (SD  =2.4) and its range was 90 to 100. Mean of Speech intelligibility percentage in boys was 97.9 and in girls was 97.9. T-test showed no significant differences (P = 074)in Speech intelligibility between boys and girls. Conclusion: According to the result, speech intelligibility in 4-5 years old children was roughly similar to the adult.